What Does it Mean To Be in the Sandwich Generation? The Lived Experiences of Selected Low-income Urban Filipino Women - Tongson, Excelsa C. (Review of Women's Studies, 2023)
This research is a first attempt to highlight a relatively unexplored social phenomenon. It examines women's experiences in the context of the types of care they provide children and elderly relatives and the support that these women receive. The phenomenon is without a local term, and this research aims to draw attention to a number of issues like poverty, intersectionality, and VAWC. This article discusses prevailing practices of gender inequality, but also examines the narratives that challenge the stereotyped images of women. It also proposes that future research must provide a compelling argument hinged on the under-fulfillment of these women caregivers' rights and the implications of gendered division of labor on their development. Testimonies and disaggregated data on age, gender, and other identities (such as issues unique to LGBT) may also paint a richer picture of their unique familial position.